Foreign Domestic Workers and Eldercare in Singapore: Who Hires Them?. Issue 3 (27th May 2019) - Rozario, Philip A.; Hong, Song-Iee
ABSTRACT: In Singapore, policy makers expect families to remain actively involved in the care of their frail older relatives, as manifestly expressed in its Many Helping Hands approach to long-term care. To enable families to fulfill this expectation, the government has enacted policies that encourage the hiring of foreign domestic workers (FDWs) to complement or supplement informal caregiving efforts. Using the Andersen Behavioral Model, we were interested in identifying caregiver and care receiver characteristics that might predict the hiring of FDWs. With data from a convenience sample of 488 informal caregivers, we ran logistic regression regressing the hiring of an FDW on various predisposing, enabling, and need factors. Of interest, enabling factors such as household income, housing type, and educational level were predictive of hiring an FDW in the home. Only one need factor, time spent in caregiving, was predictive of the increased likelihood to hire an FDW. Policies that encourage the marketization of care are likely to favor those with financial means and inadvertently ignore the caregiving burdens of lower income families. In addition, we suggest research and policies to ensure the well-being and protection of FDWs who have become a key component of the long-term care policy and practice in Singapore.